2016
DOI: 10.1523/jneurosci.0499-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Sir2/Sirt1 Links Acute Inebriation to Presynaptic Changes and the Development of Alcohol Tolerance, Preference, and Reward

Abstract: Acute ethanol inebriation causes neuroadaptive changes in behavior that favor increased intake. Ethanol-induced alterations in gene expression, through epigenetic and other means, are likely to change cellular and neural circuit function. Ethanol markedly changes histone acetylation, and the sirtuin Sir2/SIRT1 that deacetylates histones and transcription factors is essential for the rewarding effects of long-term drug use. The molecular transformations leading from short-term to long-term ethanol responses mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(113 citation statements)
references
References 67 publications
4
97
0
Order By: Relevance
“…5 Briefly, groups of 20 genetically identical flies (n = 1) were exposed to 55% ethanol vapor or 100% humidified air, and the number of flies that lost the righting reflex were counted at 6 minutes intervals. 5 Briefly, groups of 20 genetically identical flies (n = 1) were exposed to 55% ethanol vapor or 100% humidified air, and the number of flies that lost the righting reflex were counted at 6 minutes intervals.…”
Section: Ethanol Behaviorsmentioning
confidence: 99%
“…5 Briefly, groups of 20 genetically identical flies (n = 1) were exposed to 55% ethanol vapor or 100% humidified air, and the number of flies that lost the righting reflex were counted at 6 minutes intervals. 5 Briefly, groups of 20 genetically identical flies (n = 1) were exposed to 55% ethanol vapor or 100% humidified air, and the number of flies that lost the righting reflex were counted at 6 minutes intervals.…”
Section: Ethanol Behaviorsmentioning
confidence: 99%
“…Tl , cact , MyD88 , imd , rel , and Spn27a ) as ethanol responsive, and recently Troutwine et al , (2016) tested each step in the Toll pathway and showed an effect on sensitivity but not tolerance. Similarly, Sirt1 , shown to be important for tolerance, was also flagged by Morozova et al , (2006), functionally tested by Kong et al , (2010a), and later extensively studied by Engel et al , (2016). An important general observation was that gene modules associated with innate ethanol sensitivity and tolerance were distinct (Morozova et al , 2009; Morozova et al , 2011; Morozova et al , 2014).…”
Section: Genomic Analyses Of Alcohol Responses In Fliesmentioning
confidence: 99%
“…The mammalian homolog of Sir2 is called SIRT1 . Engel et al , (2016) described Sir2 ’s effect on alcohol responses in detail. Sir2 mutations perturb normal ethanol resistance, tolerance, and preference.…”
Section: Genomic Analyses Of Alcohol Responses In Fliesmentioning
confidence: 99%
“…Specifically, SIRTs are enzymes that play a role in the modification chromatin structure, which leads to long-term epigenetic changes in gene transcription and expression [26] [27]. Recent evidence suggests that an increase in SIRT1/2 subtypes enhances the rewarding effects of cocaine [25] and mediates drug-induced neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that an increase in SIRT1/2 subtypes enhances the rewarding effects of cocaine [25] and mediates drug-induced neuroplasticity. NAc SIRT 1 and 2 protein levels increase following cocaine administration [28] and Resveratrol (a SIRT1 and 2 agonist) increases the rewarding effects of cocaine [26]. Local inhibition of SIRT1 and SIRT2 in the NAc decreases cocaine reward exemplified by attenuated CPP [28].…”
Section: Introductionmentioning
confidence: 99%